The Effect of Product Innovation and Brand Image on Purchase Interest at Tiema Collection in Majalaya Sub-District - Salsabil Putri Nurdianti; r Iim Takwim (Escalate : Economics and Business Journal, 2026)
The increasingly competitive fashion industry requires businesses to continuously innovate their products and build a strong brand image in order to attract consumers. Purchasing interest is an important indicator of marketing success because it reflects consumers' interest and intention to purchase a product. Therefore, companies need to understand the factors that can influence consumer purchasing interest. This study aims to describe product innovation, brand image, and purchasing interest, as well as analyze the influence of product innovation and brand image, both partially and simultaneously, on consumer purchasing interest in Tiema Collection in Majalaya District. The research method used is a quantitative method with a descriptive and verification approach. Data were collected through the distribution of questionnaires to Tiema Collection consumers using a Likert scale, then analyzed using multiple linear regression analysis techniques. Descriptive analysis results show that product innovation is in the strong category, brand image is in the strong category, and consumer purchase interest is in the very strong category. The results of the verification analysis show that product innovation does not have a significant effect on consumer purchasing interest, even though it has a positive direction of influence. Meanwhile, brand image has a positive and significant effect on consumer purchasing interest. Furthermore, the simultaneous test results show that product innovation and brand image together have a significant effect on the purchasing interest of Tiema Collection consumers in Majalaya District. It can be concluded that brand image plays a more dominant role in influencing consumer purchase intention, while product innovation acts as a supporting factor.